1977
DOI: 10.1104/pp.60.6.903
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Concentration in Isolated Chloroplasts during Photosynthesis

Abstract: The 02 concentration in intact and osmoially disrupted isolated spinach (Spinacia oleracea, L.) chloroplasts during photosynthesis was estimated. The chloroplasts were allowed to reduce 3-phosphoglycerate, C02, or ferrcyanide in ltht until the rate of 02 production was linear.When the liht was turned off 02 evolution from the chloroplasts continued for a few seconds. This prolonged 02 evolution is due to an 02 surpus inside the chloroplas which equilibrates with that in the medium. From this surplus the 02 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 18 publications
(20 reference statements)
1
26
0
1
Order By: Relevance
“…2). Experi- [30].) This 02 affimity is similar to that previously determined for algae (22,26), but considerably lower than that reported from experiments with broken chloroplasts (2,12).…”
supporting
confidence: 53%
“…2). Experi- [30].) This 02 affimity is similar to that previously determined for algae (22,26), but considerably lower than that reported from experiments with broken chloroplasts (2,12).…”
supporting
confidence: 53%
“…The sampling system used in these experiments does not necessitate equilibration across a gas-liquid interface, but incomplete equilibration of the 02 isotopes between the inside and outside of the chloroplasts (or cells) will result in an underestimation of the rate of 02 reduction. However, the relatively simpler isolated chloroplast system and the reported (27) …”
Section: Discussionmentioning
confidence: 99%
“…We found that lamellae 02 reduction was saturated fully with respect to 02 levels as low as 155 /IM and our measurements yielded Km values of 13.5 to 22.2 ,uM (24). 02 concentrations in the illuminated intact chloroplast may rise as high as I mm (29), such that in vivo it is likely that the sites where 02 may bind to be reduced are strongly competed for by other reducible moieties, e.g. NADP and nitrite.…”
Section: Discussionmentioning
confidence: 99%